Exploring local knowledge and perceptions on zoonoses among pastoralists in northern and eastern Tanzania. - Peter Ernest Mangesho; Moses Ole Neselle; Esron D Karimuribo; James E Mlangwa; Kevin Queenan; Leonard E G Mboera; Jonathan Rushton; Richard Kock; Barbara Häsler; Angwara Kiwara; Mark Rweyemamu (Public Library of Science (PLoS), 2017)
BACKGROUND:Zoonoses account for the most commonly reported emerging and re-emerging infectious diseases in Sub-Saharan Africa. However, there is limited knowledge on how pastoral communities perceive zoonoses in relation to their livelihoods, culture and their wider ecology. This study was carried out to explore local knowledge and perceptions on zoonoses among pastoralists in Tanzania. METHODOLOGY AND PRINCIPAL FINDINGS:This study involved pastoralists in Ngorongoro district in northern Tanzania and Kibaha and Bagamoyo districts in eastern Tanzania. Qualitative methods of focus group discussions, participatory epidemiology and interviews were used. A total of 223 people were involved in the study. Among the pastoralists, there was no specific term in their local language that describes zoonosis. Pastoralists from northern Tanzania possessed a higher understanding on the existence of a number of zoonoses than their eastern districts' counterparts. Understanding of zoonoses could be categorized into two broad groups: a local syndromic framework, whereby specific symptoms of a particular illness in humans concurred with symptoms in animals, and the biomedical framework, where a case definition is supported by diagnostic tests. Some pastoralists understand the possibility of some infections that could cross over to humans from animals but harm from these are generally tolerated and are not considered as threats. A number of social and cultural practices aimed at maintaining specific cultural functions including social cohesion and rites of passage involve animal products, which present zoonotic risk. CONCLUSIONS:These findings show how zoonoses are locally understood, and how epidemiology and biomedicine are shaping pastoralists perceptions to zoonoses. Evidence is needed to understand better the true burden and impact of zoonoses in these communities. More studies are needed that seek to clarify the common understanding of zoonoses that could be used to guide effective and locally relevant interventions. Such studies should consider in their approaches the pastoralists' wider social, cultural and economic set up.